2020
DOI: 10.1136/bmjopen-2019-036720
|View full text |Cite
|
Sign up to set email alerts
|

Role of the intelligent exercise rehabilitation management system on adherence of cardiac rehabilitation in patients with coronary heart disease: a randomised controlled crossover study protocol

Abstract: IntroductionThe benefits of cardiac rehabilitation (CR) on the reduction of cardiac and all-cause mortality are well documented. However, adherence remains suboptimal in China. It is clear that traditional CR does not meet the needs of many eligible patients and innovation is required to improve its application. Home-based CR (HBCR) is a cost-effective method that may be a valuable alternative for many individuals in China. In HBCR, it is often difficult to maintain an exercise intensity that is both effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Many clinical trials devoted to improve participation and adherence rate have been introduced, such as telerehabilitation programmes with the help of social media. 31–33 Social media, which include Twitter, Instagram, YouTube and WeChat, is well accepted in public. Hence, an activity with benefit to patients with CHD health status supervised by professionals through social media would be promising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many clinical trials devoted to improve participation and adherence rate have been introduced, such as telerehabilitation programmes with the help of social media. 31–33 Social media, which include Twitter, Instagram, YouTube and WeChat, is well accepted in public. Hence, an activity with benefit to patients with CHD health status supervised by professionals through social media would be promising.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is a health priority to explore a CR exercise programme that combined with more common daily activities. Many clinical trials devoted to improve participation and adherence rate have been introduced, such as telerehabilitation programmes with the help of social media 31–33. Social media, which include Twitter, Instagram, YouTube and WeChat, is well accepted in public.…”
Section: Discussionmentioning
confidence: 99%
“…The intelligent exercise rehabilitation management system (IERMS) was designed and developed by the research group independently ( Xu et al, 2020 ). It is an integrating evaluation, guidance, monitoring, and feedback of an integrated intelligent motion rehabilitation management system.…”
Section: Methodsmentioning
confidence: 99%
“…Home-based health programs are not a novelty regarding conventional supervised therapeutics, although systematic reviews are scarce and primarily focused on specific conditions [17][18][19][20]. Nevertheless, several studies and trials have confirmed the interest and effectiveness of home-based health programs in cardiovascular rehabilitation [7,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%